2014
DOI: 10.4218/etrij.14.0113.1320
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing New Media Subscription Based on Multigroup Analysis of IPTV and DCTV

Abstract: As the Internet Protocol TV (IPTV) service enters the broadcasting market, the competition intensifies. This paper explains the factors influencing new media subscription and their influential differences on IPTV and digital cable TV (DCTV). We use the information systems success model and gratification opportunity theory to develop our research model. We sample 621 people and collect their responses through web-based measuring software. Structural model analysis shows that the willingness to subscribe to a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
14
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 32 publications
7
14
2
Order By: Relevance
“…The findings of this study are different from those of Kang et al (2014) who found that the availability of movie genres has an influence on satisfaction. This difference in findings is due to the fact that the respondents in the previous study were TV streaming, while the current research was video streaming.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The findings of this study are different from those of Kang et al (2014) who found that the availability of movie genres has an influence on satisfaction. This difference in findings is due to the fact that the respondents in the previous study were TV streaming, while the current research was video streaming.…”
Section: Discussioncontrasting
confidence: 99%
“…The findings from this test indicate that service quality is proven to have a significant effect on satisfaction, meaning that the Netflix service that is considered quality by respondents determines the level of respondent's satisfaction. The findings of this study support the research results of Kang et al (2014) and Maichael (2018) also show the same findings, where service quality has an effect on satisfaction. Quality service means that the service provides comfort and convenience for consumers to be able to enjoy the movies that are offered by the provider.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The employees see the interactiveness of e-training system as providing cushioning effect on absence of face-to-face training as found in the traditional training methods they are used to. Also, the results have confirmed the influence of interactivity on perceived ease of use and perceived usefulness which is consistent with previous findings [ 80 , 81 ]. This implies that interactiveness of the e-training system is very likely to facilitate knowledge sharing among the trainees which can influence how they navigate and make use of the system in the easiest ways.…”
Section: Discussionsupporting
confidence: 91%